Willingness to pay for renewable energy : evidence from high wind and wave energy potential areas - A.A. Azlina; Shahida Abu Bakar; Mahirah Kamaludin; Awang Noor Ghani (Penerbit Universiti Kebangsaan Malaysia, 2022)
The study aims to investigate consumers’ willingness to pay for the development of renewable energy to encourage renewable energy consumption in the long run. This study further identifies the factors that influence consumers’ willingness to pay for renewable energy. A face-to-face questionnaire, with a contingent valuation method was administered to 672 residential electricity users in the East Coast of Peninsular Malaysia, areas that have high wind and wave energy potentials with large hydropower. The findings show that the average consumers’ willingness to pay is about RM 4.90 or about USD 1.18 per month on electricity bills as a contribution to a Renewable Energy Fund. The results further show that the consumers’ willingness to pay for renewable energy is significantly influenced by the proposed bid price, income, confidence level and education. The findings may help the government in creating a useful framework to ensure sustainable development in the future.